Hospital resource use following carotid endarterectomy in 2006: analysis of the Nationwide Inpatient Sample - Young, KC (2010)
INTRODUCTION: Our objective was to outline the relationship between age and length of stay (LOS), hospital costs and discharge disposition following carotid endarterectomy (CEA). MATERIALS AND METHODS: We identified discharge records from the 2006 Nationwide Inpatient Sample (NIS). The primary outcome was LOS from the surgical procedure to discharge. We examined LOS from procedure to discharge because the time from procedure to discharge may better reflect hospital stay due to the procedure itself for subjects with symptomatic carotid artery disease rather than including days hospitalized for stroke recovery. Secondary endpoints included total LOS, discharge disposition and hospital costs. RESULTS: There were 118,218 discharge records for CEA and >90% were for asymptomatic carotid disease. The LOS from procedure to discharge and total LOS increased per decade starting with the age range of 70–79 years. Age per decade increased the likelihood of requiring a LOS from procedure to discharge of >1 day. The same trend was seen for requiring a >2 day post-operative stay. Those age ≥80 years required longer post-operative LOS compared to younger ages (OR=1.45 for >1 day and OR=1.45 for >2 days, both p<0.001). Total hospital costs averaged $10,965 for all discharges. For age dichotomized at 80 years, the average cost increased by $845. Also, age ≥80 years was independently associated with discharge to a skilled nursing facility (OR=2.4, 95% CI=2.09–2.76). DISCUSSION: Increased hospital LOS and costs were required following CEA as age increased. Morbidity following CEA should be discussed with subjects considering revascularization for asymptomatic disease.